Marriage Is Not Scary: Edukasi Kesiapan Mental dan Peran Pasangan dalam Membentuk Rumah Tangga yang Sehat pada Dewasa Awal di Kota Samarinda - Dewi, Lharasati; Nursa'adah, Yessi; Almatubah; Angriani, Bunga; Nurratuain, Davida Aufaheny; Ilman, Zidni (Community Empowerment : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2024)
Fear of marriage is increasingly common among the younger generation due to the influence of social media and cultural stigma. This fear can prevent individuals from understanding the true meaning and essence of marriage. Therefore, a sharing session “Understanding the Role of a Spouse in a Household” was held. This activity aims to provide education about emotional, spiritual, and mental readiness in marriage, as well as changing the negative paradigm about marriage. The methods used included presentations, interactive discussion, and question and answer sessions, which were delivered in an interesting manner with the support of visual media. The results of this activity showed a more positive change in the participants’ perspective toward marriage, where they were able to understand their role as a partner and the importance of commitment in building a household. With this understanding, participants are expected to be able to undergo marriage with better readiness and awareness, and build a family that is Sakinah, Mawadah, and Warahmah.